Kontrastowe nauczanie przyimków w języku angielskim i polskim – podejście glottodydaktyczne w praktyce lektora - Wargoś, Agnieszka (Neofilolog, 2026)
Prepositions are among the most challenging grammatical categories in foreign language learning due to their polysemy and limited cross-linguistic equivalence. This article aims to examine the effectiveness of a contrastive approach to teaching prepositions in English and Polish. The study is based on classroom-based observations of three learners: a Polish adult learning English, an Indonesian adult learning Polish, and a Polish secondary-school student raised in a bilingual environment. The analysis identifies recurring error patterns, their sources, and pedagogical implications. The findings indicate that contrastive instruction reduces prepositional errors and enhances learners’ metalinguistic awareness. <!--a=1-->